Copy and simulation in Plato’s Sophist - Másmela, Carlos (Estudios de Filosofía, 1997)
In The Sophist, Plato aims to determine the being of sophist. In their search, speakers recur to a method of division, thanks to which they describe the sophist as possessing an art by which he imitates reality ofentity. Contrary to Parmenides, who would deny the being of non-Being, for Plato, in image non-Being shares being and becomes absolute non-Being. In this context, the author of the article tries to understand imitation in arts by distinguishing two ways ofimitation: art of copying and simulacrum. The pretty difference between them lies in the way each one relates to the model, which after a very punctual analysis comes to be identified with the reality ofentity itself.